Pelaksanaan Program Kartu Indonesia Sehat dalam Meningkatkan Pelayanan Kesehatan di Pusat Kesehatan Masyarakat (Puskesmas) Multiwahana Kecamatan Sako Kota Palembang - Ridhuan Habena; Tia Syafitri (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This research was carried out at the Multipurpose Health Center, Sako District, Palembang City. The purpose of this study is to find out the health services provided to Healthy Indonesia Card (KIS) patients at the multivehicle health center and to find out what factors are obstacles in providing maximum service to Healthy Indonesia Card (KIS) patients at the health center. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques include primary data collection in the form of interviews and field observations, as well as secondary data collection in the form of documentation and literature studies. The determination of informants in this study uses the purposive sampling technique. The result of the analysis of this study is Health Services for KIS Patients at the Multiwahana Health Center, Sako District, Palembang City based on PERMENKES Number 04 Article (3) of 2019 concerning Minimum Service Standards (SPM). Health is assessed from the number of quality goods/services, quantity and quality of infrastructure. Health human resources and procedures for meeting standards are running well, this can be seen from the free services provided to KIS participants, namely KIS participants get basic health services at the Puskesmas free of charge, including examinations, treatments, immunizations and maternal and child health services. The provision of medicines at the Puskesmas ensures the availability of essential medicines needed by KIS participants. However, the flow of procedures and services at the multipurpose health center is quite clear, simple, not convoluted, and the officers are friendly. Then, the inhibiting factor in providing services to KIS patients is that there are still many people or patients who are not interested in the Healthy Indonesia Card program.